Functional anatomy and kinematics of the oral jaw system during terrestrial feeding in Periophthalmus barbarus. (October 2014) - Michel, Krijn B.; Adriaens, Dominique; Aerts, Peter; Dierick, Manuel; Wassenbergh, Sam Van
ABSTRACT Cover illustration. Skeletal body plan of the Atlantic mudskipper (Periophthalmus barbarus) from a lateral view. The mudskipper uses its fish feeding apparatus to successfully feed in the terrestrial environment. Each color represents a unit of fused or otherwise firmly interconnected ossified structures. Presented from a micro CT‐scan using Amira (FEI Visualization Sciences Group). See Michel et al. (pp. 1145–116010.1002/jmor.20291) for further details.